Preparation and Characterization of Large Grain UO2 for Accident Tolerant Fuel - Zhong, Yi; Gao, Rui; Li, Bingqing; Yang, Zhenliang; Huang, Qiqi; Wang, Zhiyi; Duan, Limei; Liu, Xuxu; Chu, Mingfu; Zhang, Pengcheng; Bai, Bin; Wang, Yun; et al. (Frontiers in Materials, 2021)
Large grain UO2 has a competitive advantage of good fission gas retention, which is considered as an accident tolerant fuel with great application potential. In this paper, the influence of preparation parameters such as sintering atmosphere, mixing process, powder pretreatment and grain growth additives on the grain size of UO2 is systematically studied. The result shows that the factors mentioned above have different effects on the grain size of UO2. The grain growth of UO2 pellet sintered in oxidizing atmosphere is better than those in reducing atmosphere. The wet mixing process has a significant advantage over the dry mixing process. In addition, the powder pretreatment has little effect on grain growth while the influence of additives plays the main role. Large grain UO2 pellets with uniform grain size up to 150 μm are successfully prepared. Finally, the thermophysical properties of the pellets are investigated.